EUROPEJSKI AUTONOMICZNY DIALOG SPOŁECZNY – SZANSE I ZAGROŻENIA - Surdykowska, Barbara (Zeszyty Prawnicze, 2017)
European Autonomous Social Dialogue – Chances and Threats Summary The article is about development of European social dialogue under 138 and 139 of EC Treaty. One can see clearly, that European social partners (ETUC, BusinessEurope, UEAPME, CEEP) want to achieve more independency from European Commission. This aim at development independency manifest oneself in sign of autonomous agreements which shall be implemented by national social partners in accordance with the procedures and practices specific to management and the labour in member states. So far was sung 3 cross sector autonomous agreements –Framework Agreement on Telework, Framework Agreement on the WorkRelated Stress and Framework Agreement on Harassment and Violence at Work. The article is also about first multi sector autonomous agreement on Workers’ Health Protection Through the Good Handling and Use of Crystalline Silica and Products Containing it. In Poland implementation of autonomous agreements can be seen as misgiving. In Poland intensification of social dialogue is low. Number of sectoral employer organizations is unsatisfactory. Implementation of autonomous agreements animates bilateral dialogue among employer organizations and trade unions in Poland. However if one thinks about weakness of social partner in new members states can see that it can bring to different level of protection between workers from old and new members states.